2013
DOI: 10.1007/s11136-013-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health-related quality of life 6 years after childhood cochlear implantation

Abstract: PURPOSE To examine the impact of cochlear implant (CI) intervention on health-related quality of life (HRQOL) assessed by both self- and parent-reported measures. METHODS In this national study of children implanted between ages 6 months and 5 years, HRQOL of 129 children 6-year post-CI was compared to 62 internal study (NH1) and 185 external (NH2) samples of hearing children frequency-matched to the CI group on sociodemographic variables. HRQOL ratings of children and their parents in each group, measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 59 publications
2
30
2
2
Order By: Relevance
“…Overall, there was no significant difference in QoL attainment between CI recipients and their normal-hearing peers [Clark et al, 2012;Huber, 2005;Meserole et al, 2014;Meyer et al, 2013]. Factors associated with poorer QoL outcomes included use of hearing aids (rather than a CI) [Meyer et al, 2013;Necula et al, 2013], shorter experience with an implant [Loy et al, 2010], older age at implantation [Necula et al, 2013;Schorr et al, 2009;Stacey et al, 2006;Warner-Czyz et al, 2011], additional developmental comorbidities [Sach and Barton, 2007;Edwards et al, 2012], male gender [Sach and Barton, 2007], lower auditory perception [Sach and Barton, 2007], lower parental educational level [Sach and Barton, 2007], and reduced oral communication by the child [FortunatoTavares et al, 2012].…”
Section: Summary Of Results For Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there was no significant difference in QoL attainment between CI recipients and their normal-hearing peers [Clark et al, 2012;Huber, 2005;Meserole et al, 2014;Meyer et al, 2013]. Factors associated with poorer QoL outcomes included use of hearing aids (rather than a CI) [Meyer et al, 2013;Necula et al, 2013], shorter experience with an implant [Loy et al, 2010], older age at implantation [Necula et al, 2013;Schorr et al, 2009;Stacey et al, 2006;Warner-Czyz et al, 2011], additional developmental comorbidities [Sach and Barton, 2007;Edwards et al, 2012], male gender [Sach and Barton, 2007], lower auditory perception [Sach and Barton, 2007], lower parental educational level [Sach and Barton, 2007], and reduced oral communication by the child [FortunatoTavares et al, 2012].…”
Section: Summary Of Results For Childrenmentioning
confidence: 99%
“…Eight studies reported on generic health utility metrics, which included KINDL ® [Huber, 2005;Loy et al, 2010;Warner-Czyz et al, 2009, visual analog scale (VAS) [Clark et al, 2012;Sach and Barton, 2007], Quality of Well-Being Scale (QWB) [Clark et al, 2012], Child Health and Illness Profile (CHIP) child edition [Clark et al, 2012;Meserole et al, 2014], European Quality of Life Questionnaire in 5 domains (EQ5D) [Clark et al, 2012;Sach and Barton, 2007], Satisfaction with Life Scale (SWLS) [Spencer et al, 2012], and EuroQoL VAS [Sach and Barton, 2007]. A comprehensive review of these surveys is beyond the subject of the current paper and may be found elsewhere [Froberg and Kane, 1989;Zullig et al, 2010].…”
Section: Generic Instruments In Childrenmentioning
confidence: 99%
“…The overall HRQoL for both adult and school-age prelingually deaf individuals are comparable to population norms, but decreased HRQoL has been found in the physical and psychological domains (22)(23)(24)(25). Children and parents of children with cochlear implants also report similar HRQoL to socioeconomically matched normal hearing children for many HRQoL domains, although the global HRQoL was lower in the cochlear implant group (26). More study is needed to better define the comparative HRQoL and disability of children receiving these different interventions.…”
Section: Disability-adjusted Life Yearsmentioning
confidence: 88%
“…In general, higher family stress has been negatively associated with health-related quality of life outcomes, including overall health and well-being, in families of DHH children with CI. 48 However, the levels of parenting stress experienced by parents of DHH children are unclear, with some studies reporting increased levels 49 and others showing no increase. 50,51 Consistent with our results, Pipp-Siegel et al studied 184 hearing mothers of young DHH children using the PSI-SF, finding no differences in stress levels between mothers of DHH versus NH children.…”
Section: Discussionmentioning
confidence: 99%